Exploring Sugar Levels and Glycemic Load in Honey Samples From Ikwuano, Abia State, And Umuabiara Amii Akabo, Imo State - Nnadikwe Johnson; Iheme Chigozie; Mbadike Columbus Asodike; Chinemerem Joy Johnson (BIOS: Jurnal Informatika dan Sains, 2025)
This study investigated the physicochemical properties and glycemic potential of two honey samples from Ikwuano (Umuahia) and Umuabiara Amii Akabo (Imo state). The research aimed to determine the sugar content, moisture content, pH, specific gravity, and glycemic load of the honey samples, providing valuable insights for consumers, particularly those with dietary restrictions or preferences.The results revealed significant differences in the physicochemical properties of the two honey samples. The moisture content of the Ikwuano honey was 29.5933%, while that of Umuabiara Amii Akabo was 30.4338%. The pH of Ikwuano honey was 4.28, indicating a slightly acidic nature, while that of Umuabiara Amii Akabo was 3.45, indicating a more acidic nature. The specific gravity of Ikwuano honey was 1.2680, while that of Umuabiara Amii Akabo was 1.2705, indicating a slight difference in density.The reducing sugar content was determined using lead acetate and potassium oxalate solutions, and the titration values for the Ikwuano honey and Umuabiara Amii Akabo honey were 22.0 and 19.0, respectively. The glucose content was also determined, and the glycemic load of the Ikwuano honey was found to be 46.12, while that of the Umuabiara Amii Akabo honey was 50.72.These findings suggest that the two honey samples have different glycemic potentials, with the Umuabiara Amii Akabo honey having a higher glycemic load. This information is crucial for individuals with dietary restrictions, such as those with diabetes, who need to monitor their sugar intake. Additionally, the study highlights the importance of analytical techniques in determining the quality and properties of honey samples.The research advances our understanding of the physicochemical properties and glycemic potential of honey samples from different regions, providing valuable insights for consumers, producers, and regulatory agencies. The study's findings can inform the development of guidelines for honey production and labeling, ensuring that consumers have access to accurate information about the products they consume. Furthermore, the research contributes to the growing body of knowledge on the nutritional and health benefits of honey, highlighting its potential as a natural sweetener and functional food ingredient.